2014
DOI: 10.1039/c4cc04378b
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst free silica templated porous carbon nanoparticles from bio-waste materials

Abstract: Porous Carbon Nanoparticles (PCNs) with well-developed microporosity were obtained from bio-waste oil palm leaves (OPL) using single step pyrolysis in nitrogen atmosphere at 500-600 8C in tubefurnace without any catalysis support. The key approach was using silica (SiO 2 ) bodies of OPL as a template in the synthesis of microporous carbon nanoparticles with very small particle sizes of 35-85 nm and pore sizes between 1.9-2 nm.In modern-day scientific applications, porous nanocarbons are ubiquitous and indispen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…The precursor is a biorenewable resource, areca nut kernel, and CNSs are produced by a catalyst‐free, one‐pot pyrolysis technique, ensuring cost‐effective carbon source and synthetic procedure. This work is a continuation of our previous studies on waste‐to‐wealth approach . The bio‐derived CNSs are directly used as catalytic support to Pd without any further activation, unlike the activated carbon materials that are currently in use .…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The precursor is a biorenewable resource, areca nut kernel, and CNSs are produced by a catalyst‐free, one‐pot pyrolysis technique, ensuring cost‐effective carbon source and synthetic procedure. This work is a continuation of our previous studies on waste‐to‐wealth approach . The bio‐derived CNSs are directly used as catalytic support to Pd without any further activation, unlike the activated carbon materials that are currently in use .…”
Section: Introductionmentioning
confidence: 90%
“…This work is a continuation of our previous studies on waste-to-wealth approach. [47][48][49][50][51][52] The bio-derived CNSs are directly used as catalytic support to Pd without any further activation, unlike the activated carbon materials that are currently in use. [53][54][55] We utilized microwave heating [56,57] to achieve faster conversions, unlike traditional methods.…”
Section: Introductionmentioning
confidence: 99%
“…127 Recently Gomma et al 125 reported a reasonably promising specific capacitance values using catalyst free carbon nanospheres obtained from bio-waste oil palm leaves. 127 Template method is considered as a responsible factor for increasing specific capacitance without activating carbon. Figure 22: CV curves of activated carbon nanospheres obtained from Oil palm.…”
Section: Supercapacitors From Activated Carbon Nanospheres Derived Frmentioning
confidence: 99%
“…Particularly, different synthetic routes were adopted to get the finest carbon nanoparticles (CNPs) having uniform size and shape distribution with appreciable surface area . Amongst, the pyrolysis method is relatively better than wet‐chemical process due to its high yield and reproducibility . Using pyrolytic process several attempts were made to convert malignant environmental waste into degradable/benign substances.…”
Section: Introductionmentioning
confidence: 99%